Health risk assessment of linear alkylbenzene sulfonate among snow wash workers - Nor Hidayah, Azman (2015)
The increase in car volume on the road together with existing number of cars would definitely boost with the snow wash industry, leading to increase in snow wash service. The purpose of this study was to determine the concentration of Linear Alkylbenzene Sulfonate (LAS) among snow wash workers and to determine the health risk of LAS through bioaccumulation of the chemicals in detergents used by the snow wash workers. In a survey to determine concentration of LAS, 15 respondents who works at snow wash services were interviewed on demographic information such as age, working experience, duration of works, and number of car washed per day and usage of PPE (glove), and nail samples were collected from all 10 fingers with a stainless nail cutter. The determination of LAS was performed with High Performance Liquid Chromatography (HPLC) method. Carcinogenic and non carcinogenic risks were calculated using calculation of carcinogenic indicator. The mean levels of LAS concentration among snow wash workers were 44.063 ppm. The carcinogenic risk and non carcinogenic risk of LAS were in acceptable range which were 3.660 x 106 and 4.658 x 10 which does not possess any significant risk to the workers in snow wash services. It was concluded that the snow wash workers were not get risk from the LAS chemical. There is a need for further study of LAS levels in biological samples as there have been few reports concerning LAS levels in biological samples.